Causes and Motivations of suicide in Pakistin society and Islamic teachings: پاکستانی معاشرہ میں خودکشی کے اسباب و محرکات اور اسلامی تعلیمات - Bano, Dr. Najma; Naz, Hina (Al Khadim Research Journal of Islamic Culture and Civilization, 2021)
Islam is performing its duty to guide the human beings from the very first day of the creation of universe, this process will continue till the day of judgment. Islam is the religion of peace, safety, love and care, the concept of saving the life is built on strong foundation. According to the teaching of Islam only that person is Muslim from Whom the life and property of others Muslims and non Muslims is safe and sound, the piety and safety of human life holds basic importance in Islam. To kill any body without any reason is haram and an act of paganism (Kufr). Islam makes human life respectable to desire for death is prohibited. All such incentives are discouraged which may be threat to human life. Suicide is considered an evil action in Quran and Hadith. A materialistic person as well as a materialistic nation both are the victim of disappointment. A Materialistic person depends on material resource to lead his life. He is disappointed when all these things seem useless to him. When a person is disappointed, he commits suicide and when a nation is disappointed, it is its death, that's why the concept of suicide is very horrifying in human civilization. This article will be useful for the youngesters in learning how to face life situation and difficulties bravely and avoid actions like committing suicide.